Degrees of mixture, degrees of freedom : genomics, multiculturalism, and race in Latin America - Wade, Peter, 1957- (Duke University Press, 2017)
Peter Wade draws on a multidisciplinary research study in Mexico, Brazil, and Colombia, arguing that genomics produces biologized versions of racialized difference within the nation and the region and that a comparative approach nuances the simple idea that highly racialized societies give rise to highly racialized genomics.